The transformation of agricultural counseling to the management of innovation in order to strengthen food security in the Kabupaten Dairi - Juita Rahmadani Manik (JASc (Journal of Agribusiness Sciences), 2019)
Many efforts by the government to achieve self-sufficient national bread including primary agricultural products, price subsidy fertilizer subsidy other, and factors of production inputs construction of irrigation infrastructure and transportation.Research and development counseling continued to push ( sumardjo, national food security 1999 ).According to leagans in puspadi ( 2003 ) extension role facilitate people in, learning activities that is not only in the education and ensure the adoption of new innovations, but also change the community perspective and encouraged them to improve life. Thus extension in the role of food security program in the area is very important, because as a communicator, extension the facilitator and motivator very closely related to efforts to repair, knowledge skill and. manners of societySyahyuti ( 2016 ) noted other than institutional challenges there are some things that requires agricultural extension services changed, among other things a challenge from the side of the condition of agroekologi is that counseling should be able to respond to the needs of the technology that relies heavily on different, agroekologi zone that no longer the same as in the green revolution. This report is written with a qualitative approach .Design research is a case study , by a unit analysis balai agricultural counseling .This study will design model transformation balai agricultural counseling who able to perform in the management of innovation in order to strengthen food security national .Programs established agricultural counseling the kecamatan level , bpp as the agricultural information facility , institutional development at the bpp farmers , bpp function as a place for training overall in kabupaten dairi in the category of good